Organic carbon measurements on Bute Inlet marine sediment samples - Sophie Hage; Valier Galy; Matthieu Cartigny; Catharina Heerema; Maarten S Heijnen; Sanem Acikalin; Michael A Clare; Ian J W Giesbrecht; Darren R Gröcke; Alison Hendry; R G Hilton; Stephen M Hubbard; et al. (PANGAEA, 2022)
This dataset includes organic carbon measurements on sediment samples collected in Bute Inlet (British Columbia, Canada) in October 2016 (cruise number PGC2016007) and October 2017 (cruise number PGC2017005) aboard the research vessel CCGS Vector. The cruise PGC2016007 took place between 7 October and 17 October 2016 and was led by Gwyn Lintern. The cruise PGC2017005 took place between 19 and 29 October and was led by Cooper Stacey. Marine sediment samples were collected in Bute Inlet using a box corer for the sandy samples in the submarine channel and a piston corer for the muddy samples in the overbanks and distal basin.